Central role of the ramAR locus in the multidrug resistance in ESBL-Enterobacterales - François Gravey; Alice Michel; Bénédicte Langlois; Mattéo Gérard; Sébastien Galopin; Clément Gakuba; Damien Du Cheyron; Laura Fazilleau; David Brossier; François Guérin; Jean-Christophe Giard; Simon Le Hello (Microbiology Spectrum, 2024)
ABSTRACT The aim of this study was to evaluate the proportion of resistance to a temocillin, tigecycline, ciprofloxacin, and chloramphenicol phenotype called t2c2 that resulted from mutations within the ramAR locus among extended-spectrum β-lactamases-Enterobacterales (ESBL-E) isolated in three intensive care units for 3 years in a French university hospital. Two parallel approaches were performed on all 443 ESBL-E included: (i) the minimal inhibitory concentrations of temocillin, tigecycline, ciprofloxacin, and chloramphenicol were determined and (ii) the genomes obtained from the Illumina sequencing platform were analyzed to determine multilocus sequence types, resistomes, and diversity of several tetR-associated genes including ramAR operon. Among the 443 ESBL-E strains included, isolates of Escherichia coli (n = 194), Klebsiella pneumoniae (n = 122), and Enterobacter cloacae complex (Ecc) (n = 127) were found. Thirty-one ESBL-E strains (7%), 16 K. pneumoniae (13.1%), and 15 Ecc (11.8%) presented the t2c2 phenotype in addition to their ESBL profile, whereas no E. coli presented these resistances. The t2c2 phenotype was invariably reversible by the addition of Phe-Arg-β-naphthylamide, indicating a role of resistance-nodulation-division pumps in these observations. Mutations associated with the t2c2 phenotype were restricted to RamR, the ramAR intergenic region (IR), and AcrR. Mutations in RamR consisted of C- or N-terminal deletions and amino acid substitutions inside its DNA-binding domain or within key sites of protein–substrate interactions. The ramAR IR showed nucleotide substitutions involved in the RamR DNA-binding domain. This diversity of sequences suggested that RamR and the ramAR IR represent major genetic events for bacterial antimicrobial resistance.IMPORTANCEMorbimortality caused by infectious diseases is very high among patients hospitalized in intensive care units (ICUs). A part of these outcomes can be explained by antibiotic resistance, which delays the appropriate therapy. The transferable antibiotic resistance gene is a well-known mechanism to explain the high rate of multidrug resistance (MDR) bacteria in ICUs. This study describes the prevalence of chromosomal mutations, which led to additional antibiotic resistance among MDR bacteria. More than 12% of Klebsiella pneumoniae and Enterobacter cloacae complex strains presented mutations within the ramAR locus associated with a dysregulation of an efflux pump called AcrAB-TolC and a porin: OmpF. These dysregulations led to an increase in antibiotic output notably tigecycline, ciprofloxacin, and chloramphenicol associated with a decrease of input for beta-lactam, especially temocillin. Mutations within transcriptional regulators such as ramAR locus played a major role in antibiotic resistance dissemination and need to be further explored.